Online Practicum Design (Praton) in Assisting Learning Process of Database Courses in the Information System Department, Universitas Terbuka, Indonesia - Suryadi, Andri; Sufandi, Unggul Utan; Nurdiana, Dian (International Journal of Global Operations Research, 2021)
The development of technology is an inseparable part of human life. Through its development,  technology furthermore produces various reliable tools to assist people in many ways. The technological applications can be in the forms of Google products such as  Google Classroom, Google Form, and Google meet, and also other applications such as Zoom Cloud Meeting, Microsoft Teams  intended to solve various kinds of problems including education field. These technological advancements are popularly used and are indeed very helpful in learning, but sometimes it can’t be hindered that technological applications are not always in accordance with the needs. For example, the practicum learning process in the Information Systems Study Program, Faculty of Science and Technology, Open University, which has no practical application yet. This is because the existing applications are not in accordance with the learning process at the Open University. So, the solution that must be done is to develop an online practicum application (Praton) in the Information Systems Study Program, Faculty of Science and Technology of the Open University. The process of developing a practicum application also cannot be done immediately, so at least there must be an application development design first. Application development design must go through several stages using a software development model. One of the models that can be used is the waterfall model with an object-based approach or commonly referred to as UML (Unified Modeling Language). The results of this software development design are in the form of a software design document and will be sent to a programmer to establish the application. With this application design, programmers will know more about the specifications of online practicum applications that suit the needs of learning process.